Maksimisasi Pemasaran Untuk Meningkatkan Pangsa Pasar Di Tengah Penurunan Permintaan Menggunakan Linear Programming Metode Grafik Pada UMKM UD.MURNI - Anjani, Marissa; Ayuka, Yeyen; Wicaksana Kuswara, Satria; Mardhiyah, Ainun (Shofanah Media Berkah, 2024)
This article explores the maximization of marketing strategies to enhance market share amid declining demand, specifically focusing on the micro, small, and medium enterprise (MSME) UD. Murni. The rapid economic growth in Indonesia has intensified competition, particularly following the COVID-19 pandemic, leading to operational and sales challenges for many MSMEs. This research employs linear programming through graphical methods to develop a mathematical model aimed at efficiently allocating resources in sandal and shoe production to maximize profits. The study identifies key issues faced by UD. Murni, including a lack of adaptation to online marketing trends and changing consumer preferences. By implementing innovative marketing strategies, particularly digital marketing, the research aims to improve product visibility and customer engagement, ultimately increasing sales and market share for UD. Murni.